Feasibility and Effectiveness of the Results of the Development of a Teaching Module for Writing Biographical Texts Based on Project Based Learning - Puspa, Resti May; Noermanzah, Noermanzah; Gumono, Gumono (IJLECR (International Journal of Language Education and Cultural Review), 2024)
The teaching module for writing biographical texts made by teachers at SMK Negeri 3 Kota Bengkulu is still not student-centered, making it difficult for students to write biographical texts. Therefore, it is necessary to develop a teaching module for writing biographical texts based on project-based learning. Therefore, the purpose of this study was to develop a teaching module for writing biographical texts based on project-based learning that is feasible and effective for use by teachers and students. This type of research was Research and Development model ADDIE with the following stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques in this study used documentation techniques, interviews, questionnaires, observations, and test techniques. The results of the study showed that the teaching module needed by teachers and students is a learning activity based on project-based learning. The design developed in this study consists of three important components, namely learning objectives, learning activities, and assessments. The characteristics of the development of this teaching module are at the project-based learning stage starting from determining basic questions, compiling project planning, compiling project schedules, implementing and monitoring projects, assessing project results, and evaluating experiences. The teaching module has been implemented and the results are effective to use with the results of the t-test value tcount>ttable, namely 20.66>1.68 with a Sig. value (2-tailed) of 0.001<0.05.